Effective project management : - Wysocki, Robert K. (Wiley Publishing, Inc., 2007)
This definitive guide to project management shows you how to: Take advantage of new variations on traditional project management methods, including risk assessment and control Decide the best method for managing specific types of projects by analyzing all of the pros and cons Apply the Adaptive Project Framework to the world of fast-paced, high-change, and complex projects Create a war room to successfully manage multiple team projects Determine how project portfolio management approaches can help companies achieve a greater return on investment Utilize all nine Project Management Body of Knowledge (PMBOK) standards advocated by the Project Management Institute (PMI)